Immunohistochemical and ultrastructural features of congenital melanocytic naevus cells support a stem‐cell phenotype. (13th August 2013) - Kinsler, V.A.; Anderson, G.; Latimer, B.; Natarajan, D.; Healy, E.; Moore, G.E.; Sebire, N.J.
<x xml:space="preserve">Abstract</x> What's already known about this topic? The cell of origin of congenital melanocytic naevi (CMN) is not known. Theoretical candidates proposed include mature basal layer melanocytes, direct precursors of the melanocytes destined for the basal layer (melanoblasts), or stem cells residing within the dermis. In recent years stem cells have been isolated from human hair follicles, and from non‐hair‐bearing dermis. What does this study add? A normal melanocyte population overlies many dermal CMN, leading us to hypothesize that in these cases CMN are likely to develop from a cell present in the skin independent of, or remaining after, normal melanocytic migration. Immunohistochemistry and transmission electron microscopy of CMN cells have identified stem‐cell characteristics, with differentiation towards melanocytes in the superficial dermis. These findings support the hypothesis that the cell of origin of CMN could be a cutaneous stem cell.